ARTIFICIAL INTELLIGENCE IN KOREAN LANGUAGE EDUCATION IN UZBEKISTAN: OPPORTUNITIES, CHALLENGES, AND PRACTICAL - Rizwan S.L. (International Journal of Literature and Language Studies, 2023)
rapid development of artificial intelligence (AI) technologies has significantly transformed modern educational environments, particularly in the field of foreign language education. AI-powered educational systems, intelligent tutoring platforms, speech recognition technologies, and conversational chatbots are increasingly integrated into language teaching and learning processes worldwide. Korean language education in Uzbekistan is also experiencing the impact of these technological innovations due to the growing interest in Korean language and culture, educational cooperation between Uzbekistan and the Republic of Korea, and increasing demand for Korean language specialists.